Students’ Attitude Towards Gamification-Based Teaching in Mathematics in Basic Schools - Attah, Justina Ojoma; Ogunlade, Oyeronke Olufunmilayo; Falade, Ayotunde Atanda (Indonesian Journal of Teaching in Science, 2024)
The study investigates students’ attitudes towards gamification-based teaching in mathematics in basic schools in Kwara State. The study adopted a descriptive design of the survey type. The population for this study were all junior secondary students in Kwara State. The target population for this study was all junior secondary students. A purposive sampling technique was used to select a sample size of 64 students. To ensure the validity of the instrument, a pilot study was carried out in a non-participating school outside the scope of the study and a value coefficient of .77 was obtained using Cronbach alpha. The findings of the study revealed that students in junior secondary schools had a positive attitude towards gamification-based teaching and there is no significant difference in the male and female students’ attitude towards gamification-based teaching in mathematics. The study concluded that attitudes toward gamification-based teaching had a significant impact on students' outcomes. It was therefore recommended among others that All teachers in junior secondary schools should adopt the usage of gamification-based teaching in the teaching and learning of mathematics as it can produce positive results in teaching effectiveness and student performance.